The Role of Internal and External Audit in Financial Control - Anvarovich, Bakhadirov Shokhrukhbek (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This paper aims at examining the central roles of internal and external audits in enhancing financial control mechanisms. While internal audits are assessments that occur inside the organization with the primary business of assessing internal controls, risk management, and compliance, external audits are independent ones that examine organizational financial statements for accuracy and honesty. Although these audits are defined for separate functions, there is considerable synergy for improvement in the governance and accountability when performed jointly. In light of the existing scarcity of published material on the subject, this study employs a qualitative approach with Research Design that involves a review of both academic and industry literatures, policies and guidelines, as well as case studies. From the results, internal audits improve the internal control, whilst external audits improve accountability and better adherence to rules on financial reporting. Yet there are difficulties, for example, the problem of the scarce financial and human resources, skepticism regarding the conclusions, and questions concerning auditor independence remain rather acute. It is suggested that the specific measures-simple though important, should be followed to expose audit to more people and to enhance utilization of both traditional and technology-enabling audit types. They demonstrate why audit practices must be refined by organizations and regulators, reducing excessive focus while increasing transparency. Awareness might be created for future research to undertake the analyses of integrated audit systems over time, and innovations such as artificial intelligence and blockchain in the audit practices. The outcomes of this study make a significant contribution to filling gaps in accumulated knowledge and improving the auditing approach to meet international financial regulation norms.